Issues of taxation of entrepreneurs and self-employed persons - Navro‘zova Farog‘atxon Abduxamid qizi (Genius Journals, 2024)
The article describes individual entrepreneurs and self-employed individuals. Procedural and practical recommendations were offered to increase the importance of taxation of individual incomes in the formation of budget revenues. In addition, a study was conducted on the current state of taxation of individual entrepreneurs and selfemployed persons, studies of economists were studied within the scope of the topic, and conclusions and proposals were formed.
Keywords: Personal income tax; land tax; real estate; tax